2001
DOI: 10.1097/00000542-200103000-00025
|View full text |Cite
|
Sign up to set email alerts
|

BIS Monitoring to Prevent Awareness during General Anesthesia

Abstract: The contention that Bispectral Index monitoring reduces the risk of awareness is unproven, and the cost of using it for this indication is currently unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 11 publications
0
37
0
2
Order By: Relevance
“…BIS scores range from 0 (flat line EEG) to 100 (fully awake) with values of 60-70 and greater than 70 corresponding to deep sedation and moderate sedation, respectively [29][30][31]. Initial studies of BIS or alternative EEG-based monitoring of sedation during endoscopy reported that these tools correlated well with the level of patient consciousness [32], and permitted more effective titration of propofol and faster recovery from sedation during endoscopy [33].…”
Section: Introductionmentioning
confidence: 99%
“…BIS scores range from 0 (flat line EEG) to 100 (fully awake) with values of 60-70 and greater than 70 corresponding to deep sedation and moderate sedation, respectively [29][30][31]. Initial studies of BIS or alternative EEG-based monitoring of sedation during endoscopy reported that these tools correlated well with the level of patient consciousness [32], and permitted more effective titration of propofol and faster recovery from sedation during endoscopy [33].…”
Section: Introductionmentioning
confidence: 99%
“…O'Conner et al konnten anhand einer Poweranalyse zeigen, dass in einer Studie zur Vermeidung von Awareness durch EEG-Monitoring zwischen 20.000 und 50.000 Patienten untersuchen werden müssten [58]. Dieses ist sehr aufwendig, und bisher wurden keine Studien publiziert, die dieses Kriterium erfüllen.…”
Section: Vermeidung Von Awarenessunclassified
“…As noted earlier, BIS monitoring is an adjunct to clinical judgment, not a substitute for it. However, there are certain unusual circumstances that may produce inaccurate BIS readings, and clinicians will need to know how to recognize and manage those situations (O'Connor et al, 2001).…”
Section: Clinical Responses Using Bispectral Indexmentioning
confidence: 99%